A proposed compressed air drying method using pressurized liquid desiccant and experimental verification. (1st March 2015) - Yin, Yonggao; Zheng, Baojun; Yang, Can; Zhang, Xiaosong
Highlights: A novel compressed air drying method using pressurized liquid desiccant was proposed. Experiments verified the method and get compressed air with the humidity of 0.9 g/kg. Energy efficiency was analyzed to show the energy saving potential of the new method. Abstract: A novel compressed air drying method using pressurized liquid desiccant is proposed in this paper. The compressed air drying system is consisted of a compressed air module, a pressurized liquid desiccant dehumidifier, a liquid desiccant regenerator working in an atmospheric pressure, and other auxiliary components. An experimental apparatus of the pressurized liquid desiccant dehumidifier associated with a compressed air module is established to verify the proposed air drying method experimentally. The results show that, under the pressure of 0.5 MPa, the moisture content in the outlet air can reach 0.9 g/kg. The moisture content of the outlet air reaches 1.4 g/kg under the pressure of 0.3 MPa, and the power consumption of the drying system is 6.17 kJ/g, which is 0.69 kJ/g and 10.1% lower than the conventional compressed air cooling drying system. The dehumidification efficiency is around 0.90, indicating the sufficiently mass transfer between compressed air and solution in pressurized dehumidifier. Besides, the proposed compressed air drying system can use the low-grade heat from the air compressor to regenerate the diluted desiccant solution. The novel air drying method is verified to offer very dry air for industrial application, and shows significant energy saving potential compared with the conventional compressed air cooling drying system.